Behind the Scenes of Artistic Creativity Processes of Learning Creating and Organising - Hersted, Lone (Peter Lang International Academic Publishers, 2014)
Throughout the literature of creative learning, many assumptions and even stereotypes about the artists' creativity are nurtured, often according to myths going back to the Romanticism. The authors have been investigating and describing outstanding artists' creativity and learning/working processes, asking the question: how do artists create, learn, and organise their work? This book explores these questions by means of original empirical data (interviews with 22 artists) and theoretical research in the field of the arts and creativity from a learning perspective. Findings shed an original light on how artists learn and create, and how their creative learning and change processes come about, for instance when facilitating and leading creative processes.